Development of an English Narrative Writing Book for Class XI Students - Rachmawati, Rachmawati; Khumbangly, Niran; Ha, Do Thi (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This research aims to develop an English narrative writing book for class XI students using a structured development model. Through the stages of need identification, analysis, development and product evaluation, the book is prepared taking into account quality standards and student learning needs. Book validation is carried out by subject experts, design experts, teachers and students, who state that the book is content valid and suitable for use in learning. The results of product trials showed positive responses from various parties, confirming the book's effectiveness in improving students' English narrative writing skills. The novelty of this research lies in the systematic approach in developing English narrative writing books for class XI students, which pays attention to various aspects of learning and ensures relevance to students' needs. The implication of this research is that it contributes to enriching learning resources in English subjects at the secondary school level, as well as providing meaningful guidance for the development of English learning books in the future.